2015
DOI: 10.1016/j.jneumeth.2015.06.013
|View full text |Cite
|
Sign up to set email alerts
|

Non-invasive primate head restraint using thermoplastic masks

Abstract: Background The success of many neuroscientific studies depends upon adequate head fixation of awake, behaving animals. Typically, this is achieved by surgically affixing a head-restraint prosthesis to the skull. New Method Here we report the use of thermoplastic masks to non-invasively restrain monkeys’ heads. Mesh thermoplastic sheets become pliable when heated and can then be molded to an individual monkey’s head. After cooling, the custom mask retains this shape indefinitely for day-to-day use. Results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 37 publications
0
14
0
Order By: Relevance
“…A three-dimensional printed angular adaptor was also used to adjust the penetration angle to maximize the collinearity of the saccade vectors obtained by stimulation (see below “Neurophysiological recordings”). Head restraint was realized by fitting a thermoplastic mask individually for each animal 59 .…”
Section: Methodsmentioning
confidence: 99%
“…A three-dimensional printed angular adaptor was also used to adjust the penetration angle to maximize the collinearity of the saccade vectors obtained by stimulation (see below “Neurophysiological recordings”). Head restraint was realized by fitting a thermoplastic mask individually for each animal 59 .…”
Section: Methodsmentioning
confidence: 99%
“…Drucke et al 27 used thermoplastic masks as a noninvasive mold to restrain a primate head and to enable a wide range of neuroscientific experiments. They indicated that these masks allowed for the acquisition of clearer MRI images.…”
Section: Discussionmentioning
confidence: 99%
“…A 3-D printed angular adaptor was also used to adjust the penetration angle to maximize the collinearity of the saccade vectors obtained by stimulation (see below Neurophysiological recordings ). Head restraint was realized by fitting a thermoplastic mask individually for each animal 74 .…”
Section: Methodsmentioning
confidence: 99%